2020
DOI: 10.1021/acsanm.9b02034
|View full text |Cite
|
Sign up to set email alerts
|

Deep-UV Porous AlGaN Distributed Bragg Reflectors for Deep Ultraviolet Light-Emitting Diodes and Laser Diodes

Abstract: A porous-Al0.47GaN/n-Al0.47GaN stack structure with a large refractive index contrast has been fabricated through a homoepitaxial growth process on a Si-doped n+-Al0.47GaN/n-Al0.47GaN stack structure with a simple electrochemical wet etching process. A 20-pairs porous-Al0.47GaN distributed Bragg reflector structure (DBR) with a high aluminum content was fabricated at the deep-ultraviolet wavelength region of light emitting diodes. Low compressive strain and high reflectance has been observed in a porous-AlGaN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…The n + -AlGaN:Si epitaxial layer with a high refractive index can be transformed into the conductive porous AlGaN:Si layer with a low refractive index through an electrochemical (EC) wet etched process. EC-treated porous AlGaN/AlGaN DBR had been demonstrated as a reflector in our previous report …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The n + -AlGaN:Si epitaxial layer with a high refractive index can be transformed into the conductive porous AlGaN:Si layer with a low refractive index through an electrochemical (EC) wet etched process. EC-treated porous AlGaN/AlGaN DBR had been demonstrated as a reflector in our previous report …”
Section: Introductionmentioning
confidence: 74%
“…EC-treated porous AlGaN/AlGaN DBR had been demonstrated as a reflector in our previous report. 19 In this paper, the AlGaN-based UVC resonant-cavity LED (RC-LED) structures with top and bottom pipe-AlGaN distributed Bragg reflectors (DBRs) have been fabricated. For the top/bottom pipe-AlGaN DBR structures, 20 pairs of the epitaxial n + -AlGaN:Si/n-AlGaN:Si stack structures were transformed into the pipe-AlGaN/n-AlGaN DBR structures through a doping-selective EC wet etching process.…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, Wu et al have reported the lateral electrochemically etched n + -Al 0.47 Ga 0.53 N/n-Al 0.47 Ga 0.53 N DUV NP-DBRs with 93% reflectance at 276 nm. 25 The N d of the n + -Al 0.47 GaN and n-Al 0.47 GaN layers were 2 × 10 19 and 5 × 10 18 cm −3 , respectively. Although lateral EC etching is more favorable to achieve high porosity, separated mesas that are tens to hundreds of μm wide are disadvantageous for fabricating large-scale DBRs and related devices.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Few studies have reported reflectance close to 90%, but with Al content not exceeding 15% , and stopband staying at near UV . Recently, Wu et al have reported the lateral electrochemically etched n + -Al 0.47 Ga 0.53 N/ n -Al 0.47 Ga 0.53 N DUV NP-DBRs with 93% reflectance at 276 nm . The N d of the n + -Al 0.47 GaN and n -Al 0.47 GaN layers were 2 × 10 19 and 5 × 10 18 cm –3 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As the n-doped AlGaN is selectively etched into porous morphology, a large refractive index contrast is formed between n-doped and undoped layers, and same Al content avoids lattice and thermal mismatch 11 . At present, laterally ECE and vertically-laterally ECE are the two main methods for preparing nanoporous (NP)-DBRs 12,13 . Using these two methods, GaN-based NP-DBRs have been widely reported in the blue and near-ultraviolet spectral regions [14][15][16][17] .…”
mentioning
confidence: 99%